Beyond Decoupling: Rethinking the Relationship Between the Institutional Environment and the Classroom - Coburn, Cynthia E. (Sociology of Education, 2004)
The decoupling argument—that schools respond to pressures from the institutional environment by decoupling changes in structures from classroom instruction—has been a central feature of institutional theory since the early 1970s. This study suggests the need to rethink this argument. Drawing on a study of the relationship between changing ideas about reading instruction in California from 1983 to 1999 and teachers' classroom practice, the study provides evidence that messages about instruction in the environment influence classroom practice in a process that is framed by teachers' preexisting beliefs and practices and the nature of the messages themselves. Implications are drawn for theories of teachers' autonomy and methodological approaches to studying macro-micro linkages.